TEKNIK PERBANYAKAN DAN APLIKASI PREDATOR Dolichoderus thoracicus (SMITH) (HYMENOPTERA: FORMICIDAE) UNTUK PENGENDALIAN PENGGEREK BUAH KAKAO Conopomorpha cramerella (SNELLEN) DI PERKEBUNAN RAKYAT - Alam Anshary; Flora Pasaru (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The research aim was to develop a mass rearing technique of D. thoracicus by means of creating an artificial nest and to apply such technique as means to control cocoa pod borer (CPB) in small holder plantations. The research was carried out using experimental design and survey methods. The research consisted of different stages of experiments: (i) application of the artificial nest in the cocoa plantation, (ii) data record of cocoa pod borer attack level, (iii) analysis of dispersal pattern, and (iv) analysis of the cocoa production. Results of the research showed that the population density of D. thoracicus in the artificial nest sited on the primary branch was 8-9 times (12 % - 15%) higher than that on the jetty stem and main stem. The application of D. thoracicus by the artificial nest for controlling CPB could suppress the percentage of pod borer attack by 5%, bean damage by 42.95% and bean weight reduction by 21.03%. The analysis of dispersal pattern, based on the distribution pattern by Southwood (1997) in which Z<-1.96 or x mean < S2, showed that during three periods of observations, D. thoracicus tended to cluster.